Obesity and reproductive health: "nocturne" to modern comorbidity - Mekan R. Orazov; Viktor E. Radzinsky; Vera E. Balan; Evgeny D. Dolgov (LLC "MEDIAFORMAT", 2024)
Modern trends of human lifestyle changes contribute to the unparalleled increase in the incidence of some occupational diseases. And, despite the development of modern technologies and such a pronounced leap in social development, obesity remains an unresolved issue of mankind. Today, obesity represents an overwhelming problem that needs to be solved immediately and covers many medical specialties, including gynecology. In this regard, the paper is aimed to consider epidemiological features of obesity as a global issue and report the key touchpoints with modern gynecology and key approaches to clinical management of patients of this cohort.